Deubiquitinases: Novel Therapeutic Targets in Immune Surveillance? - Gloria Lopez-Castejon; Mariola J. Edelmann (Hindawi Limited, 2016)
Inflammation is a protective response of the organism to tissue injury or infection. It occurs when the immune system recognizes Pathogen-Associated Molecular Patterns (PAMPs) or Damage-Associated Molecular Pattern (DAMPs) through the activation of Pattern Recognition Receptors. This initiates a variety of signalling events that conclude in the upregulation of proinflammatory molecules, which initiate an appropriate immune response. This response is tightly regulated since any aberrant activation of immune responses would have severe pathological consequences such as sepsis or chronic inflammatory and autoimmune diseases. Accumulative evidence shows that the ubiquitin system, and in particular ubiquitin-specific isopeptidases also known as deubiquitinases (DUBs), plays crucial roles in the control of these immune pathways. In this review we will give an up-to-date overview on the role of DUBs in the NF-κB pathway and inflammasome activation, two intrinsically related events triggered by activation of the membrane TLRs as well as the cytosolic NOD and NLR receptors. Modulation of DUB activity by small molecules has been proposed as a way to control dysregulation or overactivation of these key players of the inflammatory response. We will also discuss the advances and challenges of a potential use of DUBs as therapeutic targets in inflammatory pathologies.